2021
DOI: 10.1002/adem.202100571
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stress‐Aging Pretreatment on Hot Deformation Behavior and Microstructure Evolution of a Ni–Cr–Nb–Mo–Ti Alloy

Abstract: Hot deformation behavior and microstructure evolution of stress and stress‐free aged NiCrNbMoTi alloy are investigated by hot compressive tests. The impacts of stress aging upon the flow softening and dynamic recrystallization (DRX) behavior are analyzed. Also, the variations of dislocation substructures are studied. The basket‐weave δ‐phases induced by stress‐aging pretreatment can refine grains during hot deformation. On the one hand, the basket‐weave δ‐phases mutually intersect and form some enclosure s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…[6][7][8][9] In last few years, the microstructure evolution and thermal deformation features of nickel-based superalloys had been investigated by many researchers. [10][11][12][13][14] Additionally, many studies found that the deformation parameters significantly affect the rheological behavior and grain characteristics of nickel-based superalloys. [15,16] So, it is necessary to optimize the thermal deformation processing by systematically studying the deformation mechanisms under various processing conditions and establishing the precise model to forecast the rheological behavior of P/M superalloys.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] In last few years, the microstructure evolution and thermal deformation features of nickel-based superalloys had been investigated by many researchers. [10][11][12][13][14] Additionally, many studies found that the deformation parameters significantly affect the rheological behavior and grain characteristics of nickel-based superalloys. [15,16] So, it is necessary to optimize the thermal deformation processing by systematically studying the deformation mechanisms under various processing conditions and establishing the precise model to forecast the rheological behavior of P/M superalloys.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, considering the strong relationship between deformation mechanism and deformation conditions, it is significantly vital to understand the hot deformation behavior of segregated and nonsegregated zones for the rack steels to optimize the hot workability and rolling process. Numerous studies of the hot deformation behavior have been conducted based on flow curves and constitutive relationships in magnesium alloys, [10][11][12] stainless steels, [13][14][15] microalloyed steels, [16][17][18] and so on. However, the effect of segregation on the hot deformation behavior is rarely reported for ultraheavy steel plates.…”
Section: Introductionmentioning
confidence: 99%